What the future of AI will be like, and how it may affect UiTM and Malaysian society / Assoc. Prof. Dr Zuraida Khusaimi ... [et al.] - Khusaimi, Zuraida; Malek, Mohd Firdaus; Asli, Noor Asnida; Fadzilah Suhaimi, Mohd Husairi; Mahmood, Mohamad Rusop; Buniyamin, Irmaizatussyehdany (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
Artificial intelligence (AI) is poised to have a significant impact on society worldwide, including in Malaysia. With the rapid development of AI technology, we can expect to see many changes in the way we live and work in the coming years. As one of the largest public universities in Malaysia, Universiti Teknologi MARA (UiTM) may benefit from incorporating AI into its academic programs. However, as with any emerging technology, there are both pros and cons to consider when it comes to AI for UiTM academics. One of the most significant benefits of AI is its ability to streamline administrative tasks. This includes tasks such as grading assignments, managing student records, and scheduling appointments. By automating these tasks, UiTM academics can focus on more critical aspects of their job, such as research and teaching. AI can be used to tailor educational materials and experiences to individual students' needs. For example, it can analyze student data to identify areas where students are struggling and provide personalized recommendations to help them improve. Additionally, AI can be used to create customized learning experiences, such as virtual simulations, that are more engaging and effective than traditional classroom lectures. By using AI to personalize educational materials and experiences, UiTM academics can improve learning outcomes for their students. Additionally, AI can be used to provide immediate feedback to students, enabling them to identify areas where they need to improve and make corrections in real time.